Gingival Health Status of 12-Year-Old School Children in Jakarta: A Cross-Sectional Study - Rosalien, Robbykha; Hutami, Dina F; Agustanti, Ary; Septalita, Annisa; Adiatman, Melissa; Maharani, Diah A (Makara Journal of Health Research, 2018)
Background: Epidemiological data on gingival status in children is important because periodontal disease is one of the most prevalent diseases in Indonesia. This study aimed to assess the gingival health status and its associated factors among 12-year-old schoolchildren in Jakarta. Methods: This was a cross-sectional study of 12-year-old schoolchildren. There were 481 students who were recruited from 24 public and private junior high schools in Jakarta using multistage cluster proportional-to-size random sampling. Periodontal status was recorded using the community periodontal index based on World Health Organization standards. A self-completed questionnaire was given to the parents to collect information on children's backgrounds and oral health-related behaviours. Results: Only 3 of 478 participating children had healthy gums (no bleeding gums and no calculus). 99% of the children had bleeding gums and 84% had calculus. The prevalence of calculus was higher in girls than in boys. Periodontal status was not significantly related to tooth brushing habits or dental check-ups. Conclusions: Poor periodontal conditions were highly prevalent among 12-year-old schoolchildren in Jakarta. Oral health promotion and prevention strategies are urgently required.